Escalating Students’ Speaking Proficiency Through ELSA Digital App - Patmasari, Rosita; Zaitun, Zaitun (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This research aimed to measure whether or not students’ speaking proficiency strengthen after they were taught this skill by using ELSA speak app and to find out if this improvement affected by the utilization of ELSA speak app. This was a quantitative study applying pre-experimental research design with one group of pre and post-tests. A number of 36 students registered in the 8th grade of SMPN 34 Jakarta chosen through cluster sampling, participated as the sample of the study. Two speaking tests conducted before and after the experiment were used as the tools in collecting the data. The data were then analyzed by using quantitative computation and statistics of paired-sample test. The results of the analysis data answer the two research questions as follows: 1) students’ speaking proficiency improved after they studied speaking by using ELSA speak app in which their speaking performance in the post-test was better than in the pre-test, acknowledged by the average score gained in these two tests (89.77 in the post-test and 82.05 in the pre-test). 2) Students’ speaking achievement affected by the utilization of ELSA speak app proven by the results of paired sample-test in which the p-valued (2-sided) score (0.0161) was lower than the significance value (?=0.05). These findings confirmed that ELSA speak app was effective in escalating students’ speaking proficiency.